Neutrophils mediate Th17 promotion in COVID‐19 patients. Issue 1 (2nd December 2020) - Parackova, Zuzana; Bloomfield, Marketa; Klocperk, Adam; Sediva, Anna
Abstract: From the beginning of 2020, an urgent need to understand the pathophysiology of SARS‐CoV‐2 disease (COVID‐19), much of which is due to dysbalanced immune responses, resonates across the world. COVID‐19‐associated neutrophilia, increased neutrophil‐to‐lymphocyte ratio, aberrant neutrophil activation, and infiltration of neutrophils into lungs suggest that neutrophils are important players in the disease immunopathology. The main objective of this study was to assess the phenotypic and functional characteristics of neutrophils in COVID‐19 patients, with particular focus on the interaction between neutrophils and T cells. We hypothesize that the altered functional characteristics of COVID‐19 patient‐derived neutrophils result in skewed Th1/Th17 adaptive immune response, thus contributing to disease pathology. The expansion of G‐MDSC and immature forms of neutrophils was shown in the COVID‐19 patients. In the COVID‐19 neutrophil/T cell cocultures, neutrophils caused a strong polarity shift toward Th17, and, conversely, a reduction of IFNγ‐producing Th1 cells. The Th17 promotion was NOS dependent. Neutrophils, the known modulators of adaptive immunity, skew the polarization of T cells toward the Th17 promotion and Th1 suppression in COVID‐19 patients, contributing to the discoordinated orchestration of immune response against SARS‐CoV‐2. As IL‐17 and other Th17‐related cytokines have previously been shown to correlate with the disease severity, we suggest that targeting neutrophils and/or Th17 represents a potentially beneficial therapeutic strategy for severe COVID‐19 patients. Graphical Abstract: In COVID‐19, neutrophil‐mediated Th17 promotion may be an important driver of the disbalanced immune responses: therapeutic targeting of Th17 might ameliorate the immune‐related injury.